A társadalmi mobilitás néhány jellegzetessége a rendszerváltás óta Szabolcs-Szatmár-Bereg megyében = Characteristics of social mobility in Szabolcs-Szatmár-Bereg County after the regime change - Láczay, Magdolna (Közép-Európai Közlemények, 2018)
In the 25 years since the regime change generation shifts as well as fundamental changes in the economy and society happened. Does social mobility have characteristic role and traditions in these changes? Are there any new intergenerational or intragenerational trends? This article focuses on the emergence of the elites in Szabolcs-Szatmár-Bereg Country. Were there any significant social mobilizations in times of a generation shift? We have analysed the family and educational background of the local mayors and successful entrepreneurs based on interviews an local statistics. The goal of this research was to determine how many of these people live in or in the near vicinity of their birthplace and how much their professions differ from their parents’, what is their income and social status. We assume that after the regime change the a powers of the earlier local leaders were transferred to their children but they have different functions and different types of capital. On the downside the diminishing social mobility (status-education-income) does harm to large parts of the society.